Hopelessness as a predictor of attempted suicide among first admission patients with psychosis: A 10-year cohort study - Klonsky, E. David (2012)
Little is known about the longitudinal relationship of hopelessness to attempted suicide in psychotic disorders. The present study addresses this gap by assessing hopelessness and attempted suicide at multiple time-points over 10-years in a first-admission cohort with psychosis (n=414). Approximately 1 in 5 participants attempted suicide during the 10-year follow-up, and those who attempted suicide scored significantly higher at baseline on the Beck Hopelessness Scale. In general, a given assessment of hopelessness (i.e., baseline, 6-months, 24-months, and 48-months) reliably predicted attempted suicide up to 4–6 years later, but not beyond. Structural equation modeling indicated that hopelessness prospectively predicted attempted suicide even when controlling for previous attempts. Notably, a cut-point of 3 or greater on the Beck Hopelessness Scale yielded sensitivity and specificity values similar to those found in non-psychotic populations using a cut-point of 9. Results suggest that hopelessness in individuals with psychotic disorders confers information about suicide risk above and beyond history of attempted suicide. Moreover, in comparison to non-psychotic populations, even relatively modest levels of hopelessness appear to confer risk for suicide in psychotic disorders.